Ethidium bromide and SYBR Green I interact with lipid micelles - Garro, A. G. (2017)
Ethidium Bromide and SYBR Green I are usual examples of ligands that specifically binds to DNA by intercalation. Here we describe that micelles of gangliosides, a lipidic family of sialoglycosphingolipids which are the most important lipids in central nervous system, are able to interact with both, EtBr and SYBR Green I and fluoresce after UV light excitation. The interaction is not affected by the presence of high saline concentration (1M NaCl), a condition which dissociate potential electrostatic interaction between amino and carboxylic acid groups present in EtBr and GM1 respectively; instead, increase the fluorescense of EtBr/GM1 micelles. This result suggests that the EtBr is located inside the hydrophobic core of the micelle. Moreover, the SYBR Green I associated ganglioside micelles does not emit green light as with DNA, but there was a change in the light spectrum towards higher wave lengths, now emittingorange light. It was also found that the interaction with these dyes is not affected when the micelles were preloaded with other molecules (paclitaxel albumin). Moreover, further studies showed that this interaction is not observedwith other ionic and nonionic classic detergent micelles, and even the addition of these molecules to GM1 micelles interferes with the described EtBr / GM1 interaction.